Development Factors of Household Waste Reduction Based on the Waste Bank Program on the Quality of Area Facilities - Yasri, Ade; Sidabutar, Yuanita FD (Borong Newinera Publisher, 2024)
Implementation of environmentally friendly waste management using a community-based 3R pattern in the form of a waste bank. On-site handling or handling of waste at the source is the treatment of waste that still has economic value which is carried out before the waste reaches the disposal site. This research is descriptive and qualitative research, relying on primary and secondary data collection. Data analysis refers to regulations related to waste. Conclusions are drawn deductively. The results of the analysis show that through a participatory approach, the community is able to identify, analyze and map their own problems, potential, threats and obstacles to the waste problem, as well as find solutions to the waste problem.